Positive electrode active material, positive electrode comprising the same, and lithium secondary battery
Patent Information
- Application Number
- CN202580020301.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-12
- Filing Date
- 2025-03-12
- Publication Date
- 2026-10-20
AI Technical Summary
因此,在通过使用包括其中一次颗粒聚集而成的二次颗粒的正极活性材料并且然后轧制正极活性材料来制备电极的情况下,存在稳定性和寿命特性由于电池运行时严重的颗粒破裂和大量气体产生而劣化的问题
[0027]由于根据本发明的正极活性材料包括锂复合过渡氧化物,所述锂复合过渡金属氧化物的组成为本说明书中描述的化学式1,呈单颗粒的形式,并且具有在特定范围内的单晶形成度,因此可以改善容量和寿命特性。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
[0001] Cross-references to related applications
[0002] This application claims priority to Korean Patent Application No. 10-2024-0034208, filed on March 12, 2024, the disclosure of which is incorporated herein by reference. Technical Field
[0003] This invention relates to positive electrode active materials, as well as positive electrodes and lithium secondary batteries including the positive electrode active materials. Background Technology
[0004] With recent technological advancements and increased demands for mobile devices, the need for rechargeable batteries as an energy source has increased significantly. Among these rechargeable batteries, lithium-ion batteries, characterized by high energy density, high voltage, long cycle life, and low self-discharge rate, have been commercialized and are widely used.
[0005] Lithium-ion batteries consist of four main components: the positive electrode, the negative electrode, the separator, and the electrolyte. Among these, the positive electrode active material plays a crucial role in determining the battery's capacity, output, and lifespan. To achieve high energy density, output, and lifespan in lithium-ion batteries, improvements in the performance of the positive electrode active material are necessary; therefore, extensive research has recently been conducted to develop high-performance positive electrode active materials.
[0006] Lithium transition metal oxides have been used as positive electrode active materials for lithium secondary batteries, and among these oxides, lithium-cobalt composite metal oxides, such as LiCoO2, are mainly used due to their high operating voltage and excellent capacity characteristics. However, the use of large quantities of LiCoO2 as a power source for applications such as electric vehicles is limited because LiCoO2 has very poor thermal properties due to its unstable crystal structure caused by delithiation and is expensive.
[0007] Lithium manganese composite metal oxides (LiMnO2, LiMn2O4, etc.), lithium iron phosphate compounds (LiFePO4, etc.), or lithium nickel composite metal oxides (LiNiO2, etc.) have been developed as alternatives to LiCoO2. Among these materials, lithium nickel composite metal oxides have been more actively researched and developed, as they can easily achieve large-capacity batteries due to their high reversible capacity of approximately 200 mAh / g. However, LiNiO2 has limitations because it has worse thermal stability than LiCoO2, and when an internal short circuit occurs during charging due to external pressure, the positive electrode active material itself decomposes, leading to battery rupture and combustion.
[0008] Therefore, as a method to improve low thermal stability while maintaining the excellent reversible capacity of LiNiO2, nickel-cobalt-manganese-based lithium composite transition metal oxides in which a portion of nickel (Ni) is replaced by manganese (Mn) and cobalt (Co), or nickel-manganese-aluminum-based lithium composite transition metal oxides in which a portion of Ni is replaced by Mn and aluminum (Al) have been developed.
[0009] Regarding lithium composite transition metal oxides with high nickel content, they are in the form of secondary particles aggregated from primary particles with a fine average particle size (D50), characterized by a large specific surface area and low particle strength. Therefore, when preparing electrodes using positive electrode active materials comprising secondary particles formed from the aggregation of primary particles and then rolling the positive electrode active material, there is a problem of deterioration in stability and lifespan characteristics due to severe particle breakage and the generation of large amounts of gas during battery operation.
[0010] Therefore, there is a need to develop positive electrode active materials with high nickel content and improved stability, which can enable lithium secondary batteries with improved capacity and lifespan characteristics.
[0011] [Existing Technical Documents]
[0012] [Patent Literature]
[0013] (Patent Document 1) Korean Patent Application Publication No. 10-2023-0013396 Summary of the Invention
[0014] Technical issues
[0015] One aspect of the present invention provides a positive electrode active material capable of improving the capacity and lifespan characteristics of a battery.
[0016] Another aspect of the present invention provides a positive electrode and a secondary battery that have excellent capacity and lifespan characteristics by including the above-described positive electrode active material.
[0017] Technical solution
[0018] (1) The present invention provides a positive electrode active material comprising a lithium composite transition metal oxide having a composition represented by Chemical Formula 1, wherein the lithium composite transition metal oxide is in the form of single particles, and the lithium composite transition metal oxide has a single crystal formation degree (χ) of 0.0500 to 0.0750 according to Equation 1: [Chemical Formula 1] Li 1+x Ni a Mn b Co c Al d M 1 e M 2f O₂ wherein, in Chemical Formula 1, M 1 is at least one selected from the group consisting of zirconium (Zr), potassium (K), strontium (Sr) and barium (Ba), M 2 is at least one selected from the group consisting of boron (B), cerium (Ce), chromium (Cr), magnesium (Mg), vanadium (V), titanium (Ti), iron (Fe), zinc (Zn), silicon (Si), niobium (Nb), gallium (Ga), tin (Sn), molybdenum (Mo) and tungsten (W), and 0.00≤x≤0.10, 0.600≤a<1.000, 0.000<b<0.400, 0.000<c<0.400, 0.000<d≤0.100, 0.000<e≤0.100 and 0.000≤f≤0.010, [Equation 1] .
[0019] (2) The present invention provides the positive electrode active material according to the above (1), wherein the single crystal formation degree (χ) is in the range of 0.0550 to 0.0700.
[0020] (3) The present invention provides the positive electrode active material according to the above (1) or (2), wherein M 1 is at least one selected from Zr, Sr and Ba.
[0021] (4) The present invention provides the positive electrode active material according to any one of the above (1) to (3), wherein based on the total weight of the lithium composite transition metal oxide, the amount of M in the lithium composite transition metal oxide 1 is in the range of 500 ppm to 4,000 ppm.
[0022] (5) The present invention provides the positive electrode active material according to any one of the above (1) to (4), wherein the lithium composite transition metal oxide has an average crystallite size (α) of 170.0 nm to 300.0 nm.
[0023] (6) The present invention provides the positive electrode active material according to any one of the above (1) to (5), wherein the average particle diameter (D of the lithium composite transition metal oxide 50 ) is 3.00 μm to 5.00 μm.
[0024] (7) The present invention provides a positive electrode comprising the positive electrode active material according to any one of the above (1) to (6).
[0025] (8) The present invention provides a lithium secondary battery comprising the positive electrode described in the above (7).
[0026] Beneficial effects
[0027] Since the positive electrode active material according to the present invention comprises a lithium composite transition oxide, the lithium composite transition metal oxide having the composition of chemical formula 1 described in this specification, being in the form of single particles, and having a single crystal formation degree within a specific range, its capacity and lifetime characteristics can be improved.
[0028] Therefore, the performance of positive electrodes and secondary batteries containing the above-mentioned positive electrode active materials can be improved, especially their capacity and lifespan characteristics. Attached Figure Description
[0029] Figure 1 This is a scanning electron microscope (SEM) image of the positive electrode active material prepared in Example 1.
[0030] Figure 2 This is a SEM image of the positive electrode active material prepared in Example 2.
[0031] Figure 3 This is a SEM image of the positive electrode active material prepared in Example 3.
[0032] Figure 4 This is a SEM image of the positive electrode active material prepared in Example 4.
[0033] Figure 5 This is a SEM image of the positive electrode active material prepared in Example 5.
[0034] Figure 6 This is a SEM image of the positive electrode active material prepared in Example 6.
[0035] Figure 7 This is a SEM image of the positive electrode active material prepared in Comparative Example 1.
[0036] Figure 8 This is a SEM image of the positive electrode active material prepared in Comparative Example 2.
[0037] Figure 9 This is a SEM image of the positive electrode active material prepared in Comparative Example 3.
[0038] Figure 10 This is a SEM image of the positive electrode active material prepared in Comparative Example 4.
[0039] Figure 11 This is a SEM image of the positive electrode active material prepared in Comparative Example 5.
[0040] Figure 12 It is a graph showing the cycle capacity retention (cycle retention (%)) of batteries containing the positive electrode active material of each of the Examples and Comparative Examples. Detailed Implementation
[0041] The invention will be described in more detail below to allow for a clearer understanding of it.
[0042] It should be understood that the words or terms used in the specification and claims should not be interpreted as having the meaning defined in a common dictionary, and it should also be understood that, based on the inventor's ability to appropriately define the meaning of words or terms to best explain the principles of the invention, the words or terms should be interpreted as having a meaning consistent with their meaning in the relevant field and in the context of the technical idea of the invention.
[0043] It should also be understood that the terms "comprising," "including," or "having" in this specification specify the presence of the stated features, numbers, steps, elements, or combinations thereof, but do not exclude the presence or addition of one or more other features, numbers, steps, elements, or combinations thereof.
[0044] In this specification, "single-particle form" is the opposite of the concept of spherical secondary particles formed by the aggregation of tens to hundreds of primary particles prepared by conventional methods, where it refers to a form consisting of 30 or fewer primary particles. Specifically, the single-particle form in this invention can be a single particle consisting of one primary particle, or it can be a secondary particle formed by the aggregation of 2 to 30 primary particles.
[0045] In this specification, "primary particle" refers to the smallest particle unit identified when observing the positive electrode active material using a scanning electron microscope (SEM), and "secondary particle" refers to a secondary structure formed by the aggregation of multiple primary particles.
[0046] In this specification, "single crystal" refers to a crystal in a state where grain boundaries are not present within the particles.
[0047] In this specification, "microcrystal" refers to a particle unit having substantially the same crystal orientation.
[0048] In this specification, X-ray diffraction (XRD) analysis can be used to quantitatively analyze the "average crystallite size (α)" using copper (Cu) Kα X-rays. Specifically, the average crystallite size of the particles can be quantitatively analyzed by placing the particles to be measured in a sample holder and analyzing the diffraction pattern generated by irradiating the particles with X-rays. The sample is prepared by loading the powder sample of the target particles into the groove in the middle of a general-purpose powder sample holder, smoothing the surface with a glass slide, and aligning the sample height with the edge of the sample holder. Then, X-ray diffraction analysis is performed using a Bruker D8-E ndeavor equipped with a LynxEye XE-T position-sensitive detector (source: Cu-Kα radiation, wavelength: 1.54 Å), with a step size of 0.02° and a total scan time of approximately 20 minutes, using a fixed divergence slit (FDS) of 0.5° and a 2θ range of 15° to 80°. The measurement data were Rietveld refined, taking into account the charge at each site (+3 for metal ions at transition metal sites and +2 for Ni ions at Li sites) and cation mixing. Instrument broadening during crystallite size analysis was accounted for using the fundamental parameter method (FPA) implemented in the Bruker TOPAS program, and the entire peak within the measurement range was used during fitting. Among the peak types available in TOPAS, only the Lorentz contribution as a first-principles (FP) was used to fit the peak shape, and strain was not considered in this case.
[0049] In this specification, the amount of each element in lithium complex transition metal oxides can be measured by ICP (inductively coupled plasma) analysis using an inductively coupled plasma optical emission spectrometer (ICP-OES; Optima 7300 DV, PerkinElmer).
[0050] In this specification, the average particle size (D) of lithium composite transition metal oxides is... 50 The particle size distribution (PMD) can be defined as the particle size at 50% of the volumetric cumulative distribution on the particle size distribution curve (the curve of the particle size distribution). After dispersing the target powder in a dispersion medium, the dispersion medium is introduced into a commercial laser diffraction particle size analyzer (e.g., Microtrac, Microtrac S3500). The particle size distribution is calculated by measuring the difference in the diffraction pattern caused by particle size when the particles pass through the laser beam. The average particle size of lithium composite transition metal oxides can be measured by calculating the particle size at 50% of the volumetric cumulative distribution using the analyzer.
[0051] Positive electrode active material
[0052] The positive electrode active material according to the present invention will be described below.
[0053] The positive electrode active material according to the present invention includes a lithium composite transition metal oxide having a composition represented by the following Chemical Formula 1, wherein the lithium composite transition metal oxide is in the form of single particles, and the lithium composite transition metal oxide has a single crystal formation degree (χ) according to the following Equation 1 of 0.0500 to 0.0750.
[0054] [Chemical Formula 1]
[0055] Li 1+x Ni a Mn b Co c Al d M 1 e M 2 f O2
[0056] In Chemical Formula 1, M 1 is at least one selected from the group consisting of zirconium (Zr), potassium (K), strontium (Sr) and barium (Ba), M 2 is at least one selected from the group consisting of boron (B), cerium (Ce), chromium (Cr), magnesium (Mg), vanadium (V), titanium (Ti), iron (Fe), zinc (Zn), silicon (Si), niobium (Nb), gallium (Ga), tin (Sn), molybdenum (Mo) and tungsten (W), and 0.00≤x≤0.10, 0.600≤a<1.000, 0.000<b<0.400, 0.000<c<0.400, 0.000<d≤0.100, 0.000<e≤0.100 and 0.000≤f≤0.010, and
[0057] [Equation 1] .
[0058] In the case where the lithium composite transition metal oxide does not have the composition represented by Formula 1 described in the present specification, is not in the form of single particles, or has a single crystal formation degree of less than 0.0500 according to Equation 1 described in the present specification, there is a problem of poor capacity characteristics and fine particle generation caused by particle cracking when the positive electrode active material for preparing an electrode is rolled, and there is a problem that gas is generated when the positive electrode active material is used in a battery, thereby deteriorating the lifespan characteristics of the battery.
[0059] The present inventors have found that, for a positive electrode active material including a lithium composite transition metal oxide, wherein the lithium composite transition metal oxide has a composition represented by Formula 1 described in the present specification, is in the form of single particles, and has a single crystal formation degree of 0.0500 to 0.0750 according to Equation 1 described in the present specification, the thermal stability can be improved while the capacity characteristics are improved by adjusting the area of crystal grain boundaries, particle rupture can be suppressed when the positive electrode active material for preparing an electrode is rolled, and the amount of gas generation and unnecessary side reactions with an electrolyte solution when used in a battery can be ameliorated, thereby completing the present invention. As described above, a battery using the positive electrode active material according to the present invention can have excellent capacity characteristics and life characteristics.
[0060] The lithium composite transition metal oxide has a composition represented by the following Chemical Formula 1.
[0061] [Chemical Formula 1]
[0062] Li 1+x Ni a Mn b Co c Al d M 1 e M 2 f O2
[0063] In Chemical Formula 1, M 1 is at least one selected from Zr, K, Sr, and Ba, M 2 is at least one selected from B, Ce, Cr, Mg, V, Ti, Fe, Zn, Si, Nb, Ga, Sn, Mo, and W, 0.00≤x≤0.10, 0.600≤a<1.000, 0.000<b<0.400, 0.000<c<0.400, 0.000<d≤0.100, 0.000<e≤0.100, and 0.000≤f≤0.010, and M 1 is a doping element, wherein, specifically, M 1 is at least one selected from Zr, K, Sr, and Ba. M may be substantially contained 1 to improve capacity characteristics and life characteristics. In particular, in a case where M 1 is at least one selected from Zr, Sr, and Ba, it can improve the structural stability and life characteristics of the positive electrode active material, and can increase the single crystal formation degree by assisting crystal growth. If M 1For yttrium (Y), due to the excessive increase in the average crystallite size of lithium complex transition metal oxides, there is a problem that the single crystal formation degree (χ) of Equation 1 described in this invention is greater than 0.0750.
[0064] M 2 It is a dopant element, specifically, M 2 It is selected from at least one of B, Ce, Cr, Mg, V, Ti, Fe, Zn, Si, Nb, Ga, Sn, Mo, and W. It essentially does not contain M. 2 However, when M is included in an appropriate amount 2 When this is done, the particle shape of the positive electrode active material can be improved, and the stability of the crystal structure can be improved.
[0065] x can be greater than or equal to 0.00, 0.01, 0.02, 0.03, or 0.04, and can be less than or equal to 0.05, 0.06, 0.07, 0.08, 0.09, or 0.10. When x meets the above ranges, high capacity characteristics and high energy density per unit volume can be achieved.
[0066] 'a' is the molar ratio of nickel (Ni) in all metals other than lithium in a lithium-ion complex transition metal oxide, where 'a' can be greater than or equal to 0.600, 0.650, 0.700, 0.750, 0.800, or 0.850, and can be less than or equal to 0.900, 0.950, or less than 1.000. In particular, when 'a' is in the range of 0.800 to 0.900, high capacity characteristics can be achieved due to its high energy density.
[0067] b is the molar ratio of manganese (Mn) in all metals other than lithium in a lithium-based transition metal oxide complex. b can be greater than 0.000, 0.010 or more, 0.020 or more, 0.030 or more, 0.040 or more, or 0.050 or more, and can be less than 0.060, 0.070, 0.080, 0.090, 0.100, 0.200, 0.300 or less, or less than 0.400. When b meets the above ranges, the stability at room temperature and high temperature increases, and the decomposition reaction of the electrolyte solution can be relatively reduced.
[0068] c is the molar ratio of cobalt (Co) to all metals other than lithium in a lithium-ion complex transition metal oxide. c can be greater than 0.000, 0.010 or more, 0.020 or more, 0.030 or more, 0.040 or more, or 0.050 or more, and can be less than 0.060, 0.070, 0.080, 0.090, 0.100, 0.200, 0.300 or less, or less than 0.400. When c meets the above ranges, stability during charging and discharging processes can be improved, as can rate performance at room temperature and high temperatures.
[0069] d is the molar ratio of aluminum (Al) in all metals other than lithium in a lithium-ion composite transition metal oxide. d can be greater than 0.000, 0.001 or more, 0.002 or more, 0.003 or more, 0.004 or more, or 0.005 or more, and can be less than 0.006, 0.007, 0.008, 0.009, 0.010, 0.020, 0.030, 0.040, 0.050, 0.060, 0.070, 0.080, 0.090, or 0.100. When d meets the above ranges, the structural stability of the positive electrode active material can be improved, and the output characteristics can be improved.
[0070] e is the M of all metals other than lithium in lithium complex transition metal oxides. 1 The molar ratio, where e can be greater than 0.000, 0.001 or more, 0.002 or more, 0.003 or more, 0.004 or more, or 0.005 or more, and can be less than 0.010, 0.020, 0.030, 0.040, 0.050, 0.060, 0.070, 0.080, 0.090, or 0.100. When e meets the above ranges, it improves structural stability, reduces gas generation, improves lifetime characteristics, and can improve single crystal formation by aiding crystal growth.
[0071] f is M among all metals other than lithium in lithium complex transition metal oxides. 2 The molar ratio, where f can be greater than or equal to 0.000, 0.001, 0.002, or 0.003, and less than or equal to 0.004, 0.005, 0.007, 0.008, 0.009, or 0.010. When f meets the above ranges, the stability of the crystal structure of the positive electrode active material can be improved, and the particle shape can be improved.
[0072] a, b, c, d, e, and f can satisfy a + b + c + d + e + f = 1.
[0073] Lithium complex transition metal oxides (LCMOs) exist as single particles composed of fewer than 30 primary particles. That is, LMOs can be single particles or aggregates of 2 to 30 primary particles. The single-particle form distinguishes them from secondary particles consisting of more than 30 primary particles. In the case of LMOs as single particles, due to their excellent stability, the cathode active material, even when rolled, will not break or fracture. Therefore, side reactions between the cathode active material and the electrolyte solution can be reduced, and the lifespan characteristics of batteries using the cathode active material can be improved.
[0074] In this invention, the degree of single-crystal formation is evaluated and expressed as a parameter represented by Equation 1. The degree of single-crystal formation (χ) mentioned in this invention is based on the average size of the microcrystals constituting a single particle and the average particle size (D) of the lithium composite transition metal oxide as a single particle. 50 The value of the adjustment is such that the average crystallite size (α) within a single particle is closer to the average particle size (D) of the lithium composite transition metal oxide. 50 The higher the degree of single crystal formation, the better.
[0075] In other words, the degree of single-crystal formation described in this invention can increase as the number of microcrystals constituting a single particle decreases.
[0076] For example, the maximum value for single crystal formation is 1, which means that a single particle is composed of a microcrystal.
[0077] According to Equation 1, lithium composite transition metal oxides have a single crystal formation degree (χ) of 0.0500 to 0.0750. Specifically, when the single crystal formation degree (χ) is in the range of 0.0550 to 0.0700, the grain boundaries that act as the migration path for lithium ions can be appropriately adjusted to improve capacity characteristics and significantly improve the lifespan of the secondary battery. This is because grain fracture caused by grain boundaries can be suppressed, the grain boundary area in contact with the electrolyte solution can be reduced, and gas generation due to side reactions with the electrolyte solution is reduced during rolling to prepare electrodes or operate the battery. When the single crystal formation degree is less than 0.0500, the capacity characteristics are poor, and when rolling to prepare electrodes or operate the battery, grain fracture caused by grain boundaries occurs, and the grain boundary area in contact with the electrolyte solution increases significantly, thus leading to an increase in gas generation due to side reactions with the electrolyte solution. When the degree of single crystal formation is greater than 0.0750, there are fewer grain boundaries that serve as the migration path for lithium ions in the positive electrode active material particles, resulting in low lithium mobility. Therefore, there are problems with poor resistance characteristics and rate performance of the secondary battery.
[0078] According to an embodiment of the present invention, based on the total weight of the lithium composite transition metal oxide, M in the lithium composite transition metal oxide 1 The amount can range from 500 ppm to 4,000 ppm. Specifically, based on the total weight of the lithium complex transition metal oxide, the M in the lithium complex transition metal oxide... 1 The amount can be above 500 ppm, above 600 ppm, above 700 ppm, above 800 ppm, above 900 ppm, above 1,000 ppm, above 1,100 ppm, above 1,200 ppm, or above 1,300 ppm, and can be below 2,800 ppm, below 2,900 ppm, below 3,000 ppm, below 3,100 ppm, below 3,200 ppm, below 3,300 ppm, below 3,400 ppm, below 3,500 ppm, below 3,600 ppm, below 3,700 ppm, below 3,800 ppm, below 3,900 ppm, or below 4,000 ppm. In M 1 When the amount is within the above range, structural stability and lifespan characteristics can be improved.
[0079] According to one embodiment of the present invention, the lithium composite transition metal oxide may have an average crystallite size (α) of 170.0 nm to 300.0 nm. Specifically, the average crystallite size (α) of the lithium composite transition metal oxide may be 170.0 nm or more, 180.0 nm or more, 190.0 nm or more, 200.0 nm or more, or 210.0 nm or more, and may be 270.0 nm or less, 280.0 nm or less, 290.0 nm or less, or 300.0 nm or less. When the average crystallite size (α) is within the above range, particle breakage is suppressed compared to conventional secondary particles where primary particles aggregate, and side reactions with the electrolyte solution and gas generation are reduced, thus improving lifetime characteristics. Furthermore, capacity reduction and performance degradation due to reduced rolling density can be prevented, and output characteristics can be improved by suppressing the increase in resistance.
[0080] According to one embodiment of the present invention, lithium composite transition metal oxides may have an average particle size (D) of 3.00 μm to 5.00 μm. 50 Specifically, the average particle size (D) of lithium composite transition metal oxides 50The particle size can be 3.00 μm or larger, 3.10 μm or larger, 3.20 μm or larger, 3.30 μm or larger, 3.40 μm or larger, 3.50 μm or larger, 3.60 μm or larger, or 3.70 μm or larger, and can be less than 4.20 μm, less than 4.30 μm, less than 4.40 μm, less than 4.50 μm, less than 4.60 μm, less than 4.70 μm, less than 4.80 μm, less than 4.90 μm, or less than 5.00 μm. The average particle size (D) of lithium composite transition metal oxides... 50 Within the above range, excellent electrode density can be achieved, and capacity characteristics can be improved.
[0081] Preparation method of positive electrode active material
[0082] The above-mentioned positive electrode active material according to the present invention can be prepared by the following methods, but is not limited thereto.
[0083] The above-mentioned positive electrode active material according to the present invention can be prepared by a method for preparing positive electrode active materials, the method comprising the following steps: (A) by using lithium (Li)-containing raw materials, composite transition metal hydroxides, aluminum (Al)-containing raw materials, and M-containing raw materials. 1 (A) preparing a mixture by dry mixing of raw materials; (B) preparing a pre-sintered product by pre-sintering the mixture at a temperature of 800°C to 1,000°C; and (C) preparing a lithium composite transition metal oxide by mixing the pre-sintered product with lithium (Li)-containing raw materials and sintering at a temperature of 720°C to 900°C, wherein, in this case, M 1 It is selected from at least one of Zr, K, Sr and Ba, and the pre-sintering time is shorter than the sintering time.
[0084] The above-described positive electrode active material according to the present invention can be prepared by appropriately controlling the mixing ratio or type of raw materials.
[0085] Each step of the invention will be described in detail below.
[0086] Step (A)
[0087] This method includes dry mixing a lithium (Li)-containing raw material, a composite transition metal hydroxide, an aluminum (Al)-containing raw material, and a M-containing raw material. 1 The step (A) involves using raw materials to prepare a mixture.
[0088] The lithium composite transition metal oxide of the present invention utilizes a dry-mixing solid-phase raw material method, wherein, since no medium is used, energy from the beads is directly transferred to the raw material particles. Therefore, this method is energy-efficient and simple because it eliminates the need for medium filtration and drying processes. In contrast, in the case of using a method that prepares a mixture by wet mixing the composite transition metal hydroxide with a lithium-containing raw material, the reaction between the lithium-containing raw material and the composite transition metal hydroxide may be insufficient because the lithium-containing raw material may dissolve in the solvent instead of reacting with the composite transition metal hydroxide. Due to non-smooth particle growth, single-particle formation may not be sufficient, and when used in batteries, capacity reduction may occur due to factors such as the formation of rock salt phases caused by the need for over-sintering methods. Furthermore, due to the coexistence of secondary particle forms based on the precursor, the degree of single-crystal formation may not reach the level required by the present invention.
[0089] In selecting lithium-containing (Li), aluminum-containing (Al), and M-containing raw materials... 1 When preparing raw materials, any raw material suitable for solid-phase synthesis methods can be used without restriction. However, since residual sulfur after synthesis may cause problems in the cathode active material and sintering equipment, it is advantageous to exclude sulfate-based compounds, and specifically, compounds based on oxides, carbonates, and hydroxides can be used. Each of the raw materials and the composite transition metal hydroxides can be used in appropriate amounts, taking into account the amount of each metal element in the final prepared lithium composite transition metal oxide.
[0090] Complex transition metal hydroxides can be prepared by co-precipitation reaction while adding an aqueous solution of a complex transition metal, an ammonium cation complexing agent, and a basic compound to a reactor.
[0091] Aqueous solutions of complex transition metals can be prepared by dissolving a transition metal-containing raw material in a solvent such as water, and for example, by dissolving a nickel-containing (Ni), a cobalt-containing (Co), and a manganese-containing (Mn) raw material in water. Furthermore, if desired, the aqueous solution of transition metals may also include a metal-containing raw material.
[0092] The nickel-containing raw material can be at least one selected from NiO, Ni(OH)2, NiO·OH, NiCO3·2Ni(OH)2·4H2O, NiC2O4·2H2O, Ni(NO3)2·6H2O, nickel fatty acids, and nickel halides, and any one of them or a mixture of two or more of them can be used. Specifically, in order to obtain a composite transition metal hydroxide with a homogeneous composition, water-soluble NiSO4·6H2O can be used as the nickel-containing raw material.
[0093] The cobalt (Co)-containing raw material can be at least one selected from Co(OH)₂, Co₃O₄, CoO·OH, Co(OCOCH₃)₂·4H₂O, Co(NO₃)₂·6H₂O, or Co(SO₄)₂·7H₂O, cobalt fatty acids, and cobalt halides, and any one of them or a mixture of two or more of them can be used. Specifically, to obtain a complex transition metal hydroxide with a homogeneous composition, water-soluble CoSO₄·7H₂O can be used as the cobalt-containing raw material.
[0094] The manganese (Mn)-containing raw material can be at least one selected from MnCO3, Mn2O3, MnO2, Mn3O4, Mn(NO3)2, manganese acetate, manganese dicarboxylate, manganese citrate, manganese salts of fatty acids, manganese hydroxy oxides, and manganese halides such as manganese chloride, and any one of them or a mixture of two or more of them can be used. Specifically, in order to obtain a complex transition metal hydroxide with a homogeneous composition, water-soluble MnSO4·H2O can be used as the manganese-containing raw material.
[0095] Considering the amount of each metal element in the prepared composite transition metal hydroxide, nickel-containing (Ni), cobalt-containing (Co), and manganese-containing (Mn) raw materials can be used in appropriate amounts.
[0096] The ammonium cation complexing agent may include at least one compound selected from the group consisting of NH4OH, (NH4)2SO4, NH4NO3, NH4Cl, CH3COONH4, and NH4CO3, and may be added to the reactor in the form of a solution in which the above-mentioned compound is dissolved in a solvent. In this case, water or a mixture of water and an organic solvent (specifically, alcohols, etc.) that can be uniformly mixed with water may be used as the solvent.
[0097] The basic compound can be at least one compound selected from the group consisting of NaOH, KOH, and Ca(OH)₂, and can be added to the reactor in the form of a solution in which the above-mentioned compound is dissolved in a solvent. In this case, water or a mixture of water and an organic solvent (specifically, alcohols, etc.) that can be uniformly mixed with water can be used as the solvent.
[0098] If an aqueous solution of a complex transition metal, an ammonium cation complexing agent, and an alkaline compound are added to the reactor as described above, precursor particles in the form of complex transition metal hydroxides are formed due to the co-precipitation reaction of the transition metal in the aqueous solution of the complex transition metal.
[0099] The coprecipitation reaction can be carried out for 90 to 120 hours. Within this timeframe, the crystallinity of the precursor particles can be controlled to a sufficient degree.
[0100] In this case, the alkaline compound may be added in an amount that allows the pH of the reaction solution to fall within a desired range.
[0101] When the precursor particles are formed by the above method, the composite transition metal precursor is obtained by separating the particles from the reaction solution. Specifically, after separating the composite transition metal precursor from the reaction solution by filtering the reaction solution, the separated composite transition metal precursor may be washed and dried to obtain the composite transition metal precursor. In this case, processes such as grinding and / or classification may be performed if necessary.
[0102] According to one embodiment of the present invention, the composite transition metal hydroxide in step (A) may have a composition represented by the following Chemical Formula 2.
[0103] [Chemical Formula 2]
[0104] Ni p Mn q Co r M 3 s (OH)2
[0105] In Chemical Formula 2, M 3 is at least one selected from the group consisting of B, Ce, Cr, Mg, V, Ti, Fe, Zn, Si, Nb, Ga, Sn, Mo, and W, and 0.600≤p<1.000, 0.000<q<0.400, 0.000<r<0.400, and 0.000≤s≤0.010.
[0106] M 3 is a doping element, and specifically, M 3 may be at least one selected from the group consisting of B, Ce, Cr, Mg, V, Ti, Fe, Zn, Si, Nb, Ga, Sn, Mo, and W. M is not substantially included, 3 but when M is included in an appropriate amount, 3 the particle shape of the positive electrode active material may be improved, and the stability of the crystal structure may be enhanced.
[0107] p is the molar ratio of nickel (Ni) among all metals in the composite transition metal hydroxide, wherein p may be 0.600 or more, 0.650 or more, 0.700 or more, 0.750 or more, 0.800 or more, or 0.850 or more, and may be 0.900 or less, 0.950 or less, or less than 1.000.
[0108] q is the molar ratio of manganese (Mn) in all metals in a complex transition metal hydroxide, where q can be greater than 0, greater than 0.010, greater than 0.020, greater than 0.030, greater than 0.040, or greater than 0.050, and can be less than 0.060, less than 0.070, less than 0.080, less than 0.090, less than 0.100, less than 0.200, less than 0.300, or less than 0.400.
[0109] r is the molar ratio of cobalt (Co) in all metals in the complex transition metal hydroxide, where r can be greater than 0.000, greater than 0.010, greater than 0.020, greater than 0.030, greater than 0.040, or greater than 0.050, and can be less than 0.060, less than 0.070, less than 0.080, less than 0.090, less than 0.100, less than 0.200, less than 0.300, or less than 0.400.
[0110] s is the M among all metals in a complex transition metal hydroxide. 3 The molar ratio, where s can be greater than 0.000, greater than 0.001, greater than 0.002, or greater than 0.003, and can be less than 0.004, less than 0.005, less than 0.007, less than 0.008, less than 0.009, or less than 0.010.
[0111] The lithium (Li)-containing raw material can be at least one selected from LiOH, Li₂CO₃, LiNO₃, LiNO₂, LiOH·H₂O, LiH, LiF, LiCl, LiBr, LiI, CH₃COOLi, Li₂O, lithium acetate, lithium dicarboxylate, lithium citrate, lithium fatty acids, alkyl lithium, and lithium halides, and any one of them or a mixture of two or more of them can be used. Specifically, LiOH, which has a low melting point and excellent reactivity, can be used as a lithium (Li)-containing raw material.
[0112] The aluminum (Al)-containing raw material can be at least one selected from Al2O3, AlF3, and Al(OH)3, and any one of them or a mixture of two or more of them can be used. Specifically, Al(OH)3, which has excellent reactivity, can be used as an aluminum-containing raw material.
[0113] Contains M 1 The raw materials can be selected from those containing M 1 At least one of the oxides, hydroxides, and sulfuric acid hydrates may be used, and any one of them or a mixture of two or more of them may be used. Specifically, Zr(OH)₂ and Ba(OH)₂, which have relatively low reaction temperatures, may be used. 2· H2O or Sr(OH) 2· 8H2O can be used as a substance containing M1 raw material.
[0114] According to one embodiment of the present invention, the aluminum (Al)-containing raw material in step (A) can be mixed in an amount such that the amount of aluminum (Al) based on the total weight of the composite transition metal hydroxide is in the range of 1,000 ppm to 5,000 ppm. Specifically, the aluminum (Al)-containing raw material in step (A) can be mixed in an amount such that the amount of aluminum (Al) based on the total weight of the composite transition metal hydroxide is 1,000 ppm or more, 1,500 ppm or more, 2,000 ppm or more, or 2,500 ppm or more, and 3,000 ppm or less, 3,500 ppm or less, 4,000 ppm or less, 4,500 ppm or less, or 5,000 ppm or less. When the amount of aluminum (Al)-containing raw material is within the above range, since the aluminum (Al)-containing raw material can act as a pillar in the crystal structure of the positive electrode active material, the structural stability and lifetime characteristics can be improved.
[0115] According to one embodiment of the present invention, step (A) contains M 1 The raw materials can be such that, based on the total weight of the complex transition metal hydroxide, M 1 The amounts are mixed in the range of 500 ppm to 4,000 ppm. Specifically, the amount containing M in step (A) 1 The raw materials can be such that, based on the total weight of the complex transition metal hydroxide, M 1 The amount is 500 ppm or more, or 1,000 ppm or more, and mixed with amounts of less than 3,000 ppm, less than 3,500 ppm, or less than 4,000 ppm. In the presence of M 1 When the amount of raw materials is within the above range, it contains M. 1 Raw materials can improve structural stability and lifespan characteristics, and can increase single crystal formation by aiding crystal growth.
[0116] According to one embodiment of the present invention, a lithium (Li)-containing raw material, a composite transition metal hydroxide, and an aluminum (Al)-containing raw material can be mixed such that the molar ratio (M:Li:Al) of the transition metal (M) contained in the composite transition metal hydroxide, and the lithium (Li) and aluminum (Al) contained in the lithium (Li)-containing raw material and the aluminum (Al)-containing raw material, respectively, is in the range of 1:1:0.001 to 1:1.1:0.010. In this case, not only can excessive lithium be prevented from being inserted into the structure of the positive electrode active material, but the amount of unreacted residual lithium can also be low.
[0117] Step (B)
[0118] The method includes step (B) after step (A) preparing a pre-sintered product by pre-sintering the mixture at a temperature of 800°C to 1,000°C.
[0119] Pre-sintering can be performed at temperatures above 800°C, above 810°C, above 820°C, above 830°C, above 840°C, above 850°C, above 860°C, or above 870°C, and below 900°C, below 910°C, below 920°C, below 930°C, below 940°C, below 950°C, below 960°C, below 970°C, below 980°C, below 990°C, or below 1000°C. Single-particle lithium composite transition metal oxides can be formed by pre-sintering as described above. When the lithium composite transition metal oxide is in single-particle form, structural stability is improved to suppress particle breakage during rolling, and gas generation due to side reactions with the electrolyte solution can be reduced, thereby improving the lifespan characteristics of the secondary battery. When pre-sintering is carried out at a temperature below 800°C, there is a problem of low single crystal formation due to insufficient particle growth. When pre-sintering is carried out at a temperature above 1,000°C, there is a problem of forming rock salt phases (e.g., NiO) due to over-sintering.
[0120] According to an embodiment of the invention, pre-sintering can be performed in an oxygen atmosphere. In this case, nickel oxide as an impurity can be reduced, and sintering can be carried out more efficiently by providing sufficient oxygen for the reaction.
[0121] According to embodiments of the present invention, pre-sintering can be carried out for 4 to 9 hours. Specifically, pre-sintering can be carried out for more than 4 hours or more than 5 hours, and less than 8 hours or less than 9 hours. When the pre-sintering time meets the above range, particles with high crystallinity and appropriate size can be obtained, and production efficiency can be improved.
[0122] Step (C)
[0123] The method includes step (C) after step (B) mixing the pre-sintered product with a lithium (Li)-containing raw material and sintering it at a temperature of 720°C to 900°C to prepare a lithium composite transition metal oxide.
[0124] According to one embodiment of the present invention, the lithium-containing (Li) raw materials in step (C) can be mixed such that all metals (Ni+Co+Mn+Al+M) except lithium are present in the lithium composite transition metal oxide. 1The molar ratio of lithium to total lithium (Li) is 1:1.00 or higher, 1:1.01 or higher, 1:1.02 or higher, 1:1.03 or higher, or 1:1.04 or higher, and 1:1.05 or lower, 1:1.06 or lower, 1:1.07 or lower, 1:1.08 or lower, 1:1.09 or lower, or 1:1.10 or lower. "Total lithium (Li)" refers to the amount of lithium contained in the lithium (Li) raw material mixed during pre-sintering and sintering. Specifically, "total lithium (Li)" is the number of moles of lithium present in the lithium complex transition metal oxide when all metals except lithium present in the oxide are converted to 1 mole. When the molar ratio is within the above range, there is an effect that helps restore the crystal structure of the pre-sintered product.
[0125] The sintering in this invention is carried out at a temperature between 720°C and 900°C. Specifically, sintering can be carried out at temperatures above 720°C, above 730°C, above 740°C, above 750°C, above 760°C, above 770°C, above 780°C, above 790°C, above 800°C, above 810°C, or above 820°C, as well as below 830°C, below 840°C, below 850°C, below 860°C, below 870°C, below 880°C, below 890°C, or below 900°C. When sintering is carried out within the above ranges, since the crystal structure of the pre-sintered product is restored by the additional addition of lithium ions, the degree of deformation of the internal structure of the particles is reduced, and there is an effect of improving the capacity characteristics and structural stability of the positive electrode active material. When sintering is carried out at a temperature below 720°C, the problem is that the crystal structure of the pre-sintered product is difficult to restore because the pre-sintered product does not react sufficiently with the added lithium ions, the degree of deformation of the internal structure of the particles is not reduced, and the amount of unreacted residual lithium is high. When sintering is carried out at a temperature above 900°C, the problem is that rock salt phases, such as NiO, are formed due to over-sintering, and the amount of residual lithium is high.
[0126] According to an embodiment of the invention, sintering can be performed in an oxygen atmosphere. In this case, nickel oxide as an impurity can be reduced, and sintering can be carried out more efficiently by providing sufficient oxygen for the reaction.
[0127] According to embodiments of the present invention, sintering is carried out for 5 to 20 hours. Specifically, sintering can be carried out for more than 5 hours, or more than 6 hours, and for less than 12 hours, less than 13 hours, less than 14 hours, less than 15 hours, less than 16 hours, less than 17 hours, less than 18 hours, less than 19 hours, or less than 20 hours. When sintering meets the above time ranges, particles with high crystallinity and appropriate size can be obtained, and production efficiency can be improved.
[0128] In this invention, the pre-sintering time is shorter than the sintering time. This results in the following advantages: the crystal structure is synthesized at high temperature in a relatively short time through pre-sintering, while the crystal structure of the pre-sintered product is slowly restored over a relatively long time through sintering. When the sintering time is shorter than the pre-sintering time, the crystal structure of the positive electrode active material is difficult to restore, leading to poor capacity and lifetime characteristics.
[0129] According to an embodiment of the invention, pre-sintering can be performed at a higher temperature than sintering. In this case, since pre-sintering (i.e., the synthesis of crystal structures and particle growth) requires higher energy, the degree of single crystal formation can be adjusted by performing pre-sintering at a higher temperature than sintering.
[0130] positive electrode
[0131] Next, the positive electrode according to the present invention will be described.
[0132] The positive electrode according to the present invention comprises a positive electrode active material layer containing the positive electrode active material according to the present invention. Specifically, the positive electrode comprises a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector and containing the positive electrode active material. Since the positive electrode active material has been described above, its detailed description will be omitted, and only the remaining configurations will be described in detail below.
[0133] The positive electrode current collector is not particularly limited, as long as it is conductive and does not cause chemical changes in the battery. Materials used include, for example, stainless steel, aluminum, nickel, titanium, sintered carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. Furthermore, the positive electrode current collector typically has a thickness from 3 μm to 500 μm, and microscopic irregularities can be formed on the surface of the current collector to improve the adhesion of the positive electrode active material. The positive electrode current collector can be used in various shapes, such as films, sheets, foils, meshes, porous bodies, foams, nonwoven fabrics, etc.
[0134] In addition to the positive electrode active material powder, the positive electrode active material layer may optionally include conductive materials and a binder. In this case, based on the total weight of the positive electrode active material layer, the positive electrode active material can be included in an amount of 80% to 99% by weight, more specifically 85% to 98.5% by weight, and excellent capacity characteristics can be obtained within this range.
[0135] Conductive agents are used to provide conductivity to the electrodes. Any conductive agent can be used without particular limitation, as long as it has suitable electronic conductivity without causing chemical changes in the battery. Specific examples of conductive agents can be graphite, such as natural or artificial graphite; carbon-based materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fibers; powders or fibers of metals (such as copper, nickel, aluminum, and silver); conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, and any one or a mixture of two or more of them. Based on the total weight of the positive electrode active material layer, the binder content can be from 0.1% by weight to 15% by weight.
[0136] The adhesive improves the adhesion between the positive electrode active material particles and the adhesion between the positive electrode active material and the current collector. Specific examples of the adhesive may be polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof, and any one of them or a mixture of two or more of them may be used. Based on the total weight of the positive electrode active material layer, the adhesive content may be from 0.1% by weight to 15% by weight.
[0137] The positive electrode can be prepared according to typical methods for preparing a positive electrode, the difference being the use of the aforementioned positive electrode active material. Specifically, a composition for forming the positive electrode active material layer, prepared by dissolving or dispersing the aforementioned positive electrode active material, along with optional binders and conductive agents, in a solvent, is applied to the positive electrode current collector. The positive electrode can then be prepared by drying and rolling the coated positive electrode current collector. In this case, the type and amount of the positive electrode active material, binder, and conductive agent are the same as those previously described. Alternatively, as another method, the positive electrode can be prepared by casting the composition for forming the positive electrode active material layer onto a separate carrier, and then pressing the film layer, separated from the carrier, onto the positive electrode current collector.
[0138] The solvent can be one commonly used in the art and can include dimethyl sulfoxide (DMSO), isopropanol, N-methylpyrrolidone (NMP), acetone, or water, and any one of them or a mixture of two or more of them can be used. Considering the coating thickness and manufacturing yield of the slurry, the amount of solvent used may be sufficient if it can dissolve or disperse the positive electrode active material, conductive agent, and binder, and allows for a viscosity that can provide excellent thickness uniformity during subsequent coatings used to prepare the positive electrode.
[0139] Lithium secondary batteries
[0140] Next, the lithium secondary battery according to the present invention will be described.
[0141] This invention can prepare an electrochemical device including a positive electrode. The electrochemical device can specifically be a battery or a capacitor, and more specifically a lithium secondary battery.
[0142] A lithium secondary battery specifically includes a positive electrode, a negative electrode facing the positive electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte. Since the positive electrode is the same as described above, its detailed description will be omitted, and only the remaining configurations will be described in detail below.
[0143] In addition, the lithium secondary battery may optionally include a battery container that houses an electrode assembly containing a positive electrode, a negative electrode and a separator, as well as a sealing member that seals the battery container.
[0144] In a lithium secondary battery, the negative electrode includes a negative electrode current collector and a layer of negative electrode active material disposed on the negative electrode current collector.
[0145] There are no particular limitations on the negative electrode current collector, as long as it has high conductivity without causing chemical changes in the battery. Materials used include, for example, copper, stainless steel, aluminum, nickel, titanium, sintered carbon, or copper or stainless steel and aluminum-cadmium alloys surface-treated with carbon, nickel, titanium, silver, etc. Furthermore, the negative electrode current collector typically has a thickness from 3 μm to 500 μm, and similar to the positive electrode current collector, microscopic irregularities can be formed on the surface of the current collector to improve the adhesion of the negative electrode active material. For example, the negative electrode current collector can be used in various shapes, such as films, sheets, foils, meshes, porous bodies, foams, nonwoven fabrics, etc.
[0146] In addition to the negative electrode active material, the negative electrode active material layer may optionally include a binder and a conductive agent.
[0147] Compounds capable of reversibly inserting and deintercalating lithium can be used as anode active materials. Specific examples of anode active materials can be carbonaceous materials, such as artificial graphite, natural graphite, graphitized carbon fibers, and amorphous carbon; metallic compounds that can form alloys with lithium, such as silicon (Si), aluminum (Al), tin (Sn), lead (Pb), zinc (Zn), bismuth (Bi), indium (In), magnesium (Mg), gallium (Ga), cadmium (Cd), Si alloys, Sn alloys, or Al alloys; and metal oxides that can be doped or undoped with lithium, such as SiO₂. β (0<β<2), SnO2, vanadium oxide and lithium vanadium oxide; or composite materials including metal compounds and carbonaceous materials, such as Si-C composites or Sn-C composites, and any one or a mixture of two or more thereof can be used. Additionally, thin films of metallic lithium can be used as the negative electrode active material. Furthermore, both low-crystallinity carbon and high-crystallinity carbon can be used as carbon materials. Typical examples of low-crystallinity carbon can be soft carbon and hard carbon, and typical examples of high-crystallinity carbon can be irregular, planar, sheet-like, spherical or fibrous natural or artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitch-based carbon fibers, mesophase carbon microspheres, mesophase pitch and high-temperature sintered carbon, such as coke derived from petroleum or coal tar pitch.
[0148] Based on the total weight of the negative electrode active material layer, the content of the negative electrode active material can be from 80% to 99% by weight.
[0149] Adhesives are components that facilitate adhesion between conductive materials, active materials, and current collectors. Based on the total weight of the negative electrode active material layer, adhesives are typically added in amounts ranging from 0.1% to 10% by weight. Examples of adhesives include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile rubber, fluororubber, and various copolymers thereof.
[0150] A conductive agent is a component used to further improve the conductivity of the negative electrode active material. Based on the total weight of the negative electrode active material layer, the content of the conductive agent can be less than 10% by weight, specifically less than 5% by weight. There are no particular limitations on the conductive agent, as long as it is conductive without causing chemical changes in the battery. For example, conductive materials such as: graphite, such as natural or artificial graphite; carbon black, such as acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers, such as carbon fibers or metal fibers; fluorocarbons; metal powders, such as aluminum powder and nickel powder; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or polyphenylene derivatives.
[0151] The negative electrode active material layer can be prepared by coating a composition for forming the negative electrode active material layer onto a negative electrode current collector and drying the coated negative electrode current collector, wherein the composition for forming the negative electrode active material layer is prepared by dissolving or dispersing an optional binder and conductive agent, as well as the negative electrode active material, in a solvent; or it can be prepared by casting the composition for forming the negative electrode active material layer onto a separate carrier and then pressing the film layer, which is separated from the carrier, onto the negative electrode current collector.
[0152] In lithium-ion secondary batteries, the separator separates the negative and positive electrodes and provides a path for lithium ions to move. Any separator can be used without particular limitation, as long as it is commonly used in lithium-ion secondary batteries. In particular, separators with high water retention capacity for the electrolyte and low resistance to electrolyte ion transfer are preferred. Specifically, porous polymer membranes can be used, such as porous polymer membranes prepared from polyolefin-based polymers (e.g., ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers, and ethylene / methacrylate copolymers), or laminated structures having two or more layers. Furthermore, typical porous nonwoven fabrics can be used, such as nonwoven fabrics formed from high-melting-point glass fibers or polyethylene terephthalate fibers. In addition, coated separators including ceramic components or polymer materials can be used to ensure heat resistance or mechanical strength, and separators with single-layer or multi-layer structures can optionally be used.
[0153] Furthermore, the electrolyte used in this invention may include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, or molten inorganic electrolytes that can be used to prepare lithium secondary batteries, but this invention is not limited thereto.
[0154] Specifically, the electrolyte may contain organic solvents and lithium salts.
[0155] Any organic solvent can be used without particular limitation, as long as it serves as a medium through which ions involved in the electrochemical reactions of the battery can move. Specifically, ester-based solvents, such as methyl acetate, ethyl acetate, γ-butyrolactone, and ε-caprolactone; ether-based solvents, such as dibutyl ether or tetrahydrofuran; ketone-based solvents, such as cyclohexanone; aromatic solvents, such as benzene and fluorobenzene; or carbonate-based solvents, such as dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (EMC), ethylene carbonate (EC), and propylene carbonate (PC); alcohol-based solvents, such as ethanol and isopropanol; nitriles, such as R-CN (where R is a straight-chain, branched, or cyclic C2-C20 hydrocarbon group and may include double-bonded aromatic rings or ether bonds); amides, such as dimethylformamide; dioxolane, such as 1,3-dioxolane; or sulfolane can be used as organic solvents. Among these solvents, carbonate solvents are preferred, and mixtures of cyclic carbonates (e.g., ethylene carbonate or propylene carbonate) with high ionic conductivity and high dielectric constant and low viscosity linear carbonate compounds (e.g., ethyl methyl carbonate, dimethyl carbonate, or diethyl carbonate) are even more preferred, as this can improve the charge / discharge performance of the battery. In this case, the performance of the electrolyte solution can be excellent when cyclic carbonates and linear carbonates are mixed in a volume ratio of about 1:1 to about 1:9.
[0156] Lithium salts can be used without any specific limitations, as long as they are compounds capable of providing lithium ions for lithium secondary batteries. Specifically, LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2 can be used as lithium salts. Lithium salts can be used in concentration ranges from 0.1 M to 5.0 M, particularly from 0.1 M to 3.0 M. If the concentration of the lithium salt is within the above range, excellent electrolyte performance can be obtained due to the electrolyte having suitable conductivity and viscosity, and lithium ions can move efficiently.
[0157] To improve battery life characteristics, suppress battery capacity reduction, and improve battery discharge capacity, in addition to the electrolyte components mentioned above, the electrolyte may also include at least one additive, such as compounds based on haloalkyl carbonates like difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glycol dimethyl ether, triammonium hexaphosphate, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolides, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride. In this case, the additive may be included in an amount of 0.1 wt% to 10 wt%, specifically 0.1 wt% to 5 wt%, based on the total weight of the electrolyte.
[0158] Because lithium secondary batteries containing the positive electrode active material according to the present invention as described above exhibit excellent lifespan and capacity characteristics, they are suitable for portable devices such as mobile phones, laptops, and digital cameras, as well as electric vehicles such as hybrid electric vehicles (HEVs).
[0159] Therefore, according to another embodiment of the present invention, a battery module including the lithium secondary battery as a unit battery and a battery pack including the battery module are provided.
[0160] Battery modules or battery packs can be used as a power source for at least one medium-sized and large unit of power tools; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles and plug-in hybrid electric vehicles (PHEVs); or power storage systems.
[0161] The shape of the lithium secondary battery of the present invention is not particularly limited, but it can be cylindrical, prismatic, pouch-shaped or coin-shaped.
[0162] The lithium secondary battery according to the present invention can be used not only in battery cells used as power sources for small devices, but also as unit batteries in medium and large battery modules comprising multiple battery cells.
[0163] In the following, examples of the invention will be described in detail in a manner readily practiced by those skilled in the art. However, the invention can be embodied in many different forms and should not be construed as limited to the examples set forth herein. Detailed Implementation
[0164] Preparation Example
[0165] A 4 M composite transition metal aqueous solution was prepared by mixing NiSO4·6H2O, CoSO4·7H2O, and MnSO4·H2O in distilled water to achieve a nickel:cobalt:manganese molar ratio of 89:5:6. The pH of the solution was adjusted to 11 by stirring the mixture at 50 °C. Then, 10 L of the composite transition metal aqueous solution was mixed with 5 L / hr of 4 M NaOH aqueous solution and 2 L / hr of 0.4 M NH4OH aqueous solution, followed by a co-precipitation reaction for 90 to 100 hours to prepare a solution containing Ni... 0.89 Co 0.05 Mn 0.06 (OH)2 represents a complex transition metal hydroxide composition (average particle size (D) 50 (4.0μm).
[0166] Examples and Comparative Examples
[0167] Example 1
[0168] The composite transition metal hydroxide Ni prepared through the mixing preparation examples 0.89 Co 0.05 Mn 0.06 (OH)2, LiOH, and Al(OH)3 make the molar ratio of (Ni+Co+Mn):Li:Al 1:1.03:0.005, and mix Zr(OH)2 to make Ni-based 0.89 Co 0.05 Mn 0.06 A mixture was prepared with a total weight of (OH)2 and a Zr content of 1,400 ppm. In this case, Al(OH)3 was mixed in, resulting in a Ni-based mixture. 0.89 Co 0.05 Mn 0.06 The total weight of (OH)2 and the amount of Al are 2,900 ppm.
[0169] The mixture was pre-sintered at 870°C in an oxygen atmosphere for 6 hours to prepare a pre-sintered product.
[0170] Lithium composite transition metal oxide (positive electrode active material) in single-particle form was prepared by mixing LiOH with the pre-sintered product to achieve a molar ratio of (Ni+Co+Mn+Al+Zr) to total Li ((Ni+Co+Mn+Al+Zr):Li) of 1:1.04, and sintering the mixture at 820°C for 10 hours in an oxygen atmosphere.
[0171] Example 2
[0172] The composite transition metal hydroxide Ni prepared through the mixing preparation examples 0.89 Co 0.05 Mn 0.06(OH)2, LiOH, and Al(OH)3 make the molar ratio of (Ni+Co+Mn):Li:Al 1:1.01:0.005, and mix Zr(OH)2 to make Ni-based 0.89 Co 0.05 Mn 0.06 A mixture was prepared with a total weight of (OH)2 and a Zr content of 1,400 ppm. In this case, Al(OH)3 was mixed in, resulting in a Ni-based mixture. 0.89 Co 0.05 Mn 0.06 The total weight of (OH)2 and the amount of Al are 2,900 ppm.
[0173] The mixture was pre-sintered at 900°C in an oxygen atmosphere for 8 hours to prepare a pre-sintered product.
[0174] Lithium composite transition metal oxide (positive electrode active material) in single-particle form was prepared by mixing LiOH with the pre-sintered product to achieve a molar ratio of (Ni+Co+Mn+Al+Zr) to total Li ((Ni+Co+Mn+Al+Zr):Li) of 1:1.04, and sintering the mixture at 820°C for 12 hours in an oxygen atmosphere.
[0175] Example 3
[0176] The composite transition metal hydroxide Ni prepared through the mixing preparation examples 0.89 Co 0.05 Mn 0.06 (OH)2, LiOH, and Al(OH)3 make the molar ratio of (Ni+Co+Mn):Li:Al 1:1.03:0.005, and mix Zr(OH)2 to make Ni-based 0.89 Co 0.05 Mn 0.06 A mixture was prepared with a total weight of (OH)2 and a Zr content of 2800 ppm. In this case, Al(OH)3 was mixed in, making Ni-based... 0.89 Co 0.05 Mn 0.06 The total weight of (OH)2 and the amount of Al are 2,900 ppm.
[0177] The mixture was pre-sintered at 870°C in an oxygen atmosphere for 6 hours to prepare a pre-sintered product.
[0178] Lithium composite transition metal oxide (positive electrode active material) in single-particle form was prepared by mixing LiOH with the pre-sintered product to achieve a molar ratio of (Ni+Co+Mn+Al+Zr) to total Li ((Ni+Co+Mn+Al+Zr):Li) of 1:1.04, and sintering the mixture at 820°C for 10 hours in an oxygen atmosphere.
[0179] Example 4
[0180] The composite transition metal hydroxide Ni prepared through the mixing preparation examples 0.89 Co 0.05 Mn 0.06 (OH)2, LiOH, and Al(OH)3 make the molar ratio of (Ni+Co+Mn):Li:Al 1:1.03:0.005, and mix Zr(OH)2 to make Ni-based 0.89 Co 0.05 Mn 0.06 A mixture was prepared with a total weight of (OH)2 and a Zr content of 1,400 ppm. In this case, Al(OH)3 was mixed in, resulting in a Ni-based mixture. 0.89 Co 0.05 Mn 0.06 The total weight of (OH)2 and the amount of Al are 2,900 ppm.
[0181] The mixture was pre-sintered at 900°C in an oxygen atmosphere for 5 hours to prepare a pre-sintered product.
[0182] Lithium composite transition metal oxide (positive electrode active material) in single-particle form was prepared by mixing LiOH with the pre-sintered product to achieve a molar ratio of (Ni+Co+Mn+Al+Zr) to total Li ((Ni+Co+Mn+Al+Zr):Li) of 1:1.04, and sintering the mixture at 830°C for 6 hours in an oxygen atmosphere.
[0183] Example 5
[0184] The composite transition metal hydroxide Ni prepared through the mixing preparation examples 0.89 Co 0.05 Mn 0.06 (OH)2, LiOH, and Al(OH)3 make the molar ratio of (Ni+Co+Mn):Li:Al 1:1.03:0.005, and mix Ba(OH)2·H2O to make Ni-based 0.89 Co 0.05 Mn 0.06 A mixture was prepared by adding Al(OH)₂ by weight and Ba by amount of 1,400 ppm. In this case, Al(OH)₃ was mixed, resulting in a Ni-based mixture. 0.89 Co0.05 Mn 0.06 The total weight of (OH)2 and the amount of Al are 2,900 ppm.
[0185] The mixture was pre-sintered at 900°C in an oxygen atmosphere for 6 hours to prepare a pre-sintered product.
[0186] Lithium composite transition metal oxide (positive electrode active material) in single-particle form was prepared by mixing LiOH with the pre-sintered product to achieve a molar ratio of (Ni+Co+Mn+Al+Ba) to total Li ((Ni+Co+Mn+Al+Ba):Li) of 1:1.04, and sintering the mixture at 820°C for 10 hours in an oxygen atmosphere.
[0187] Example 6
[0188] The composite transition metal hydroxide Ni prepared through the mixing preparation examples 0.89 Co 0.05 Mn 0.06 (OH)2, LiOH, and Al(OH)3 make the molar ratio of (Ni+Co+Mn):Li:Al 1:1.03:0.005, and mix Sr(OH)2·8H2O to make Ni-based 0.89 Co 0.05 Mn 0.06 A mixture was prepared with a total weight of (OH)2 and an Sr content of 1,400 ppm. In this case, Al(OH)3 was mixed in, resulting in a Ni-based mixture. 0.89 Co 0.05 Mn 0.06 The total weight of (OH)2 and the amount of Al are 2,900 ppm.
[0189] The mixture was pre-sintered at 900°C in an oxygen atmosphere for 6 hours to prepare a pre-sintered product.
[0190] Lithium composite transition metal oxide (positive electrode active material) in single-particle form was prepared by mixing LiOH with the pre-sintered product to achieve a molar ratio of (Ni+Co+Mn+Al+Sr) to total Li ((Ni+Co+Mn+Al+Ba):Sr) of 1:1.04, and sintering the mixture at 820°C for 10 hours in an oxygen atmosphere.
[0191] Comparative Example 1
[0192] The composite transition metal hydroxide Ni prepared through the mixing preparation examples 0.89 Co 0.05 Mn 0.06(OH)₂, LiOH, and Al(OH)₃ result in a (Ni+Co+Mn):Li:Al molar ratio of 1:1.04:0.005. In this case, the mixing of Al(OH)₃ results in a Ni-based... 0.89 Co 0.05 Mn 0.06 The total weight of (OH)2 and the amount of Al are 970 ppm.
[0193] The mixture was pre-sintered at 750°C in an oxygen atmosphere for 6 hours to prepare a pre-sintered product.
[0194] Lithium composite transition metal oxide (positive electrode active material) in the form of secondary particles was prepared by sintering the pre-sintered product at 700°C for 10 hours in an oxygen atmosphere.
[0195] Comparative Example 2
[0196] The composite transition metal hydroxide Ni prepared through the mixing preparation examples 0.89 Co 0.05 Mn 0.06 (OH)2, LiOH, and Al(OH)3 make the molar ratio of (Ni+Co+Mn):Li:Al 1:1.03:0.005, and mix Zr(OH)2 to make Ni-based 0.89 Co 0.05 Mn 0.06 A mixture was prepared with a total weight of (OH)2 and a Zr content of 1,400 ppm. In this case, Al(OH)3 was mixed in, resulting in a Ni-based mixture. 0.89 Co 0.05 Mn 0.06 The total weight of (OH)2 and the amount of Al are 2,900 ppm.
[0197] The mixture was pre-sintered at 750°C in an oxygen atmosphere for 6 hours to prepare a pre-sintered product.
[0198] Lithium composite transition metal oxide (positive electrode active material) in single-particle form was prepared by mixing LiOH with the pre-sintered product to achieve a molar ratio of (Ni+Co+Mn+Al+Zr) to total Li ((Ni+Co+Mn+Al+Zr):Li) of 1:1.04, and sintering the mixture at 700°C for 10 hours in an oxygen atmosphere.
[0199] Comparative Example 3
[0200] The composite transition metal hydroxide Ni prepared through the mixing preparation examples 0.89 Co 0.05 Mn 0.06(OH)2, LiOH, and Al(OH)3 make the molar ratio of (Ni+Co+Mn):Li:Al 1:1.04:0.005, and mix Zr(OH)2 to make Ni-based 0.89 Co 0.05 Mn 0.06 A mixture was prepared with a total weight of (OH)2 and a Zr content of 1,400 ppm. In this case, Al(OH)3 was mixed in, resulting in a Ni-based mixture. 0.89 Co 0.05 Mn 0.06 The total weight of (OH)2 and the amount of Al are 2,900 ppm.
[0201] The mixture was pre-sintered at 900°C in an oxygen atmosphere for 10 hours to prepare a pre-sintered product.
[0202] Lithium composite transition metal oxide (positive electrode active material) in single-particle form was prepared by sintering the pre-sintered product at 830°C for 6 hours in an oxygen atmosphere.
[0203] Comparative Example 4
[0204] The composite transition metal hydroxide Ni prepared through the mixing preparation examples 0.89 Co 0.05 Mn 0.06 (OH)₂, LiOH, and Al(OH)₃ result in a (Ni+Co+Mn):Li:Al molar ratio of 1:1.04:0.005. In this case, the mixing of Al(OH)₃ results in a Ni-based... 0.89 Co 0.05 Mn 0.06 The total weight of (OH)2 and the amount of Al are 2,900 ppm.
[0205] The mixture was pre-sintered at 800°C in an oxygen atmosphere for 15 hours to prepare a pre-sintered product.
[0206] Lithium composite transition metal oxide (positive electrode active material) in single-particle form was prepared by sintering the pre-sintered product at 700°C for 20 hours in an oxygen atmosphere.
[0207] Comparative Example 5
[0208] The composite transition metal hydroxide Ni prepared through the mixing preparation examples 0.89 Co 0.05 Mn 0.06 (OH)₂, LiOH, and Al(OH)₃ result in a (Ni+Co+Mn):Li:Al molar ratio of 1:1.04:0.005. In this case, the mixing of Al(OH)₃ results in a Ni-based... 0.89Co 0.05 Mn 0.06 The total weight of (OH)2 and the amount of Al are 2,900 ppm.
[0209] The mixture was pre-sintered at 880°C in an oxygen atmosphere for 5 hours to prepare a pre-sintered product.
[0210] Lithium composite transition metal oxide (positive electrode active material) in single-particle form was prepared by sintering the pre-sintered product at 800°C for 10 hours in an oxygen atmosphere.
[0211] Experimental Example
[0212] Experimental Example 1: ICP Analysis
[0213] After taking 0.1 g of each positive electrode active material prepared in the examples and comparative examples, 1 ml of hydrochloric acid was added and heated to dissolve each positive electrode active material. Subsequently, a small amount of hydrogen peroxide was added to promote the reaction and completely dissolve the positive electrode active material to prepare a solution. The solution was then diluted with deionized water to a total volume of 10 ml to prepare the analytical sample. The weight ratio of the constituent elements present in the analytical sample was measured using an inductively coupled plasma (ICP) instrument (PerkinElmer, OPTIMA 7300 DV), and the composition of the lithium complex transition metal oxide and the amount of zirconium (ppm) are presented in Table 1 below.
[0214] [Table 1]
[0215] Table 1 confirms that the lithium composite transition metal oxides prepared in Examples 1 to 6 have the composition represented by Chemical Formula 1 as described in this invention, and based on the total weight of the lithium composite transition metal oxides, M 1 The amount was in the range of 500 ppm to 4,000 ppm. It was confirmed that the lithium composite transition metal oxides prepared in Comparative Examples 1, 4 and 5 did not have the composition represented by Chemical Formula 1 as described in this invention.
[0216] Experiment Example 2: SEM Analysis
[0217] SEM images of each positive electrode active material prepared in the examples and comparative examples were obtained using a scanning electron microscope (SEM) (JEOL, Ltd., JSM7610F) and are shown below. Figures 1 to 11 middle.
[0218] Figure 1 This is a SEM image of the positive electrode active material prepared in Example 1.
[0219] Figure 2This is a SEM image of the positive electrode active material prepared in Example 2.
[0220] Figure 3 This is a SEM image of the positive electrode active material prepared in Example 3.
[0221] Figure 4 This is a SEM image of the positive electrode active material prepared in Example 4.
[0222] Figure 5 This is a SEM image of the positive electrode active material prepared in Example 5.
[0223] Figure 6 This is a SEM image of the positive electrode active material prepared in Example 6.
[0224] Figure 7 This is a SEM image of the positive electrode active material prepared in Comparative Example 1.
[0225] Figure 8 This is a SEM image of the positive electrode active material prepared in Comparative Example 2.
[0226] Figure 9 This is a SEM image of the positive electrode active material prepared in Comparative Example 3.
[0227] Figure 10 This is a SEM image of the positive electrode active material prepared in Comparative Example 4.
[0228] Figure 11 This is a SEM image of the positive electrode active material prepared in Comparative Example 5.
[0229] according to Figures 1 to 11 It was confirmed that the positive electrode active materials prepared in Examples 1 to 6 and the positive electrode active materials prepared in Comparative Examples 2 to 5 according to the present invention are in the form of single particles. It was confirmed that the positive electrode active material prepared in Comparative Example 1 is in the form of secondary particles.
[0230] In addition, through Figures 1 to 6 It was confirmed that the positive electrode active materials prepared in Examples 1 to 6 have a relatively uniform particle size, without fine particles or large particles formed by the aggregation of many particles.
[0231] Experiment Example 3: XRD Analysis
[0232] After X-ray diffraction (XRD) measurements were performed on each positive electrode active material prepared in the Examples and Comparative Examples, the average crystallite size (α) is presented in Table 2 below.
[0233] In this case, XRD measurements were performed using a Bruker AXS D4 Endeavor. 2 g to 3 g of positive electrode active material particles were collected from each positive electrode active material powder, and XRD was measured in the 2θ range of 15° to 80° using Cu-Kα radiation (wavelength 1.54 Å, accelerating voltage 40 kV, current 40 mA) at a scan rate of 0.2° / sec.
[0234] Experiment Example 4: Average Particle Size Measurement
[0235] To measure the average particle size (D) of each positive electrode active material particle prepared in the examples and comparative examples 50 The particle size was measured using a particle size analyzer (PSA) (Microtrac, S3500), and the single crystal formation degree was calculated according to Equation 1 described in this specification. The average particle size (D) was then calculated. 50 The single crystal formation degree (χ) and single crystal formation degree are presented in Table 2 below.
[0236] [Table 2]
[0237] According to Table 2, the positive electrode active materials of Examples 1 to 6 were confirmed to have an average crystallite size (α) of 170.0 nm to 300.0 nm and an average particle size (D) of 3.00 μm to 5.00 μm. 50 Furthermore, the degree of single crystal formation (χ) was confirmed to be between 0.0500 and 0.0750. In contrast, the positive electrode active materials of Comparative Examples 1 and 2 were confirmed to have an average crystallite size (α) of less than 170.0 nm and a degree of single crystal formation (χ) of less than 0.0500, and the positive electrode active materials of Comparative Examples 3 and 4 were confirmed to have an average crystallite size (α) of greater than 300.0 nm and a degree of single crystal formation (χ) of greater than 0.0750.
[0238] Through the examples and comparative examples, it can be understood that the single crystal formation degree (χ) according to Equation 1 described in this specification is a technical feature that occurs by comprehensively controlling the sintering, sintering and pre-sintering temperatures, sintering time and the amount of raw materials added when preparing the positive electrode active material.
[0239] Experiment Example 5: Battery Characteristic Evaluation
[0240] Preparation of coin-type half-cell
[0241] A positive electrode slurry was prepared by mixing 95% by weight of each positive electrode active material prepared in the examples and comparative examples, 2.0% by weight of carbon black as a conductive agent, and 3.0% by weight of polyvinylidene fluoride (PVDF) as a binder in an N-methylpyrrolidone (NMP) solvent. The positive electrode slurry prepared above was coated on one surface of an aluminum current collector, dried at 100°C, and then rolled to prepare each positive electrode.
[0242] A lithium metal electrode is used as the negative electrode, and the electrode assembly is prepared by placing a porous polyethylene membrane between the positive and negative electrodes. A coin-shaped half-cell is prepared by placing the electrode assembly in a battery casing and injecting an electrolyte solution in which 1.0 M LiPF6 is dissolved in an organic solvent in which ethylene carbonate (EC): ethyl methyl carbonate (EMC): diethyl carbonate (DEC) are mixed in a volume ratio of 3:4:3.
[0243] Battery performance evaluation
[0244] The coin-shaped half-cell prepared as described above was charged to 4.25 V (cutoff current: 0.05 C) at 45 °C in constant current (CC) (0.1 C) - constant voltage (CV) mode, and discharged to 2.5 V in CC (0.1 C) mode to perform the formation process.
[0245] After the formation process, the coin-type half-cell was charged to 4.25 V at 25°C in CC(0.1 C)-CV (cutoff current: 0.05 C) mode and discharged to 2.5 V in CC(0.1 C) mode, and the discharge capacity was measured under these conditions. The measured discharge capacity (mAh / g) is presented in Table 3 below.
[0246] [Table 3]
[0247] According to Table 3, it was confirmed that the battery containing the positive electrode active material of Examples 1 to 6, i.e., the positive electrode active material having a single crystal formation degree (χ) of less than 0.0500 or greater than 0.0750, has a higher discharge capacity compared to the battery containing the positive electrode active material of Comparative Examples 1 to 4, i.e., the positive electrode active material not having the composition represented by Chemical Formula 1 described in this specification. Therefore, it can be understood that since the positive electrode active material according to the present invention can ensure the optimal movement path of lithium ions during insertion and extraction by controlling the grain boundaries that act as the movement path of lithium ions in the positive electrode active material particles, the capacity characteristics are improved.
[0248] Lifetime characteristics assessment
[0249] Using the coin-shaped half-cells prepared as described above, each coin-shaped half-cell was charged (0.5 C) to 4.25 V in CC-CV mode at 45°C, and then discharged (1.0 C) to 3.0 V in CC mode as one cycle. This was repeated for a total of 50 charge-discharge cycles. After measuring the discharge capacity from the 1st to the 50th cycle, the percentage of the discharge capacity in the nth cycle (n being 1 to 50) relative to the measured discharge capacity in the 1st cycle (capacity retention rate (%)) was calculated. Figure 12 The diagram shows the capacity retention (cycle retention (%)) of each battery based on the positive electrode active material, including examples and comparative examples.
[0250] according to Figure 12 It was confirmed that batteries containing the positive electrode active materials of Examples 1 to 6 have better lifespan characteristics than batteries containing the positive electrode active materials of Comparative Examples 1 to 5.
Claims
1. A positive electrode active material, comprising: a lithium composite transition metal oxide having a composition represented by Chemical Formula 1, wherein the lithium composite transition metal oxide is in the form of a single particle, and the lithium composite transition metal oxide has a single crystal formation degree (χ) according to Equation 1 of 0.0500 to 0.0750: [Chemical Formula 1] Li 1+x Ni a Mr b Co c Al d M 1 e M 2 f O2 in, In Chemical Formula 1, M 1 It is selected from at least one of the group consisting of zirconium (Zr), potassium (K), strontium (Sr), and barium (Ba). M 2 It is selected from at least one of the following groups: boron (B), cerium (Ce), chromium (Cr), magnesium (Mg), vanadium (V), titanium (Ti), iron (Fe), zinc (Zn), silicon (Si), niobium (Nb), gallium (Ga), tin (Sn), molybdenum (Mo), and tungsten (W). 0.0≤x≤0.1, 0.600≤a<1.000, 0.000<b<0.400, 0.000<c<0.400, 0.000<d≤0.100, 0.000<e≤0.100, and 0.000≤f≤0.010, [Equation 1] 。 2. The positive electrode active material according to claim 1, wherein, The single crystal formation degree (χ) is 0.0550 to 0.0700.
3. The positive electrode active material according to claim 1, wherein, M 1 It is selected from at least one of the group consisting of Zr, Sr and Ba.
4. The positive electrode active material according to claim 1, wherein, Based on the total weight of the lithium composite transition metal oxide, M in the lithium composite transition metal oxide 1 The amount ranges from 500 ppm to 4000 ppm.
5. The positive electrode active material according to claim 1, wherein, The average crystallite size α of the lithium composite transition metal oxide is 170.0 nm to 300.0 nm.
6. The positive electrode active material according to claim 1, wherein, The average particle size D of the lithium composite transition metal oxide 50 The range is from 3.00 μm to 5.00 μm.
7. A positive electrode, comprising the positive electrode active material according to any one of claims 1 to 6.
8. A lithium secondary battery, comprising the positive electrode according to claim 7.
Citation Information
Patent Citations
Positive electrode active material for lithium secondary battery, preparing method of the same
KR1020230013396A
Dome reinforced shell for pressure vessel and method for manufacturing same
KR1020240034208A